Modulation of Type III Secretion System in Pseudomonas aeruginosa: Involvement of the PA4857 Gene Product - Zhu, Miao; Zhao, Jingru; Kang, Huaping; Kong, Weina; Zhao, Yuanyu; Wu, Min; Liang, Haihua (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosais an opportunistic pathogen that causes serious acute or chronic infections in humans.Acute infections typically involve the type Ш secretion systems (T3SS) and bacterial motility,whereas chronic infectionsare often associated with biofilm formation and the type VI secretion system (T6SS). To identifynew genes required for pathogenesis, a transposon mutagenesis library was constructed and the gene PA4857, named tspR, was found to modulateT3SS gene expression. Deletion of P. aeruginosa tspRreduced the virulence in a mouse acute lung infection model and diminished cytotoxicity. Suppression of T3SS gene expression in the tspR mutant resulted from compromised translation of the T3SS master regulator ExsA. TspR negatively regulated two small RNAs, RsmYand RsmZ, which control RsmA. Our data demonstrated that defects inT3SS expression and biofilm formation in retS mutant could be partially restored by overexpression of tspR. Taken together, our results demonstrated thatthe newly identifiedretS-tspRpathway is coordinated with the retS-gacSsystem, which regulates the genes associated with acute and chronic infections andcontrols the lifestyle choice of P. aeruginosa.